2003
DOI: 10.1097/00000478-200305000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Intraparenchymal Nevus Cell Aggregates in Lymph Nodes: A Possible Diagnostic Pitfall With Malignant Melanoma and Carcinoma

Abstract: It is well documented that nevus cells can be found within the fibrous capsule and trabeculae of lymph nodes; however, it is less well known that nevus cells can also be found in the lymph node parenchyma. We report the findings in 13 cases of nevus cell aggregates located within the cortical and/or medullary parenchyma of lymph nodes. Seven of the 13 patients had a primary diagnosis of melanoma, three had no known malignancy, one had breast carcinoma, one had adnexal carcinoma of the skin, and one had squamou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
129
0
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(139 citation statements)
references
References 43 publications
2
129
0
8
Order By: Relevance
“…2,4,6 This theory would explain the presence of melanocytes in lymph nodes from pigs devoid of melanocytic cutaneous lesions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,4,6 This theory would explain the presence of melanocytes in lymph nodes from pigs devoid of melanocytic cutaneous lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the ''benign metastasis theory''-that is, nevus cells that enter dermal lymphatics and travel to assign residency in the draining lymph nodes-has been proposed to explain why benign nevus cells are sometimes found in the lymph nodes draining cutaneous nevi. 2,4,6 The benign metastasis theory also seems probable in pigs, when considering that the melan A-/PNL2-reactive cells in the trabecular sinuses were uniform, without signs of malignant behavior, and melan A-reactive melanocytes were also seen in trabecular sinuses of lymph nodes from pigs with no cutaneous melanocytic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combined MART-1-MIB-1 can improve the distinction between proliferating melanocytes in metastases and proliferating lymphocytes or histiocytes. 144 Just as HMB-45 does not label intradermal nevi, Biddle et al 178 found that an intranodal nevus is negative for HMB-45, unless it is a nodal blue nevus. Therefore, detection of HMB-45 in the melanocytic aggregate supports a diagnosis of metastatic melanoma; however, as mentioned previously, HMB-45 does not detect all metastatic melanomas, and its absence does not exclude melanoma.…”
Section: Melanoma Prognosismentioning
confidence: 99%